2017
DOI: 10.1111/pce.12977
|View full text |Cite
|
Sign up to set email alerts
|

Plant dual‐specificity tyrosine phosphorylation‐regulated kinase optimizes light‐regulated growth and development in Arabidopsis

Abstract: Light controls vegetative and reproductive development of plants. For a plant, sensing the light input properly ensures coordination with the ever-changing environment. Previously, we found that LIGHT-REGULATED WD1 (LWD1) and LWD2 regulate the circadian clock and photoperiodic flowering. Here, we identified Arabidopsis YET ANOTHER KINASE1 (AtYAK1), an evolutionarily conserved protein and a member of dual-specificity tyrosine phosphorylation-regulated kinases (DYRKs), as an interacting protein of LWDs. Our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 61 publications
(147 reference statements)
1
18
0
Order By: Relevance
“…Therefore, the TOR pathway is likely to act as a central integrator of the hormone crosstalk regulating meristem activity (Barrada et al, 2015) together with the control of cell cycle effectors as we have shown in this work. Interestingly, YAK1 interacts with circadian clock components and is required for the optimization of photomorphogenesis and reproductive development (Huang et al, 2017), underscoring the role of YAK1 in shoot and flower development, two processes also regulated by TOR (Bakshi et al, 2017;Deprost et al, 2007;Moreau et al, 2012;Ren et al, 2012). At the metabolic level, TOR and YAK1 have antagonist roles in the regulation of triacylglycerol accumulation in algae (Imamura et al, 2016;Kajikawa et al, 2015;Prioretti et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, the TOR pathway is likely to act as a central integrator of the hormone crosstalk regulating meristem activity (Barrada et al, 2015) together with the control of cell cycle effectors as we have shown in this work. Interestingly, YAK1 interacts with circadian clock components and is required for the optimization of photomorphogenesis and reproductive development (Huang et al, 2017), underscoring the role of YAK1 in shoot and flower development, two processes also regulated by TOR (Bakshi et al, 2017;Deprost et al, 2007;Moreau et al, 2012;Ren et al, 2012). At the metabolic level, TOR and YAK1 have antagonist roles in the regulation of triacylglycerol accumulation in algae (Imamura et al, 2016;Kajikawa et al, 2015;Prioretti et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…1A). Because yak1 loss-of-function T-DNA insertion mutants have previously been reported ( yak1-1, yak1-2 and yak1-3; Huang et al, 2017;Kim et al, 2015), the new alleles were named yak1-4, yak1-5 and yak1-6 and a new loss-of-function T-DNA mutant was named yak1-7 ( Fig. 1A,B).…”
Section: Mutations In the Yak1 Gene Cause Resistance To The Tor Inhibmentioning
confidence: 99%
See 1 more Smart Citation
“…They play distinct role in constitutive and alternative splicing as well as RNA metabolism (Haynes & Iakoucheva, ). A recent study in Arabidopsis revealed that a dual‐specificity tyrosine phosphorylation regulated kinase binds with LWD1 and monitors light‐dependent growth and development (Huang et al, ). We observed the precise tyrosine phosphorylation sites of LWD1 and LWD13 and demonstrated dehydration‐responsive alteration in their phosphorylation status.…”
Section: Discussionmentioning
confidence: 99%
“…We observed the precise tyrosine phosphorylation sites of LWD1 and LWD13 and demonstrated dehydration‐responsive alteration in their phosphorylation status. Previously, LWD1 and LWD13 were implicated in light‐dependent plant growth and development (Huang et al, ), besides photoperiod sensing and flowering (Wu, Wang, & Wu, ). However, they have never been reported to participate in stress response, particularly dehydration.…”
Section: Discussionmentioning
confidence: 99%